Оптимизация и аппаратурно-технологическое оформление процесса первичной конденсации агрегатов синтеза аммиака - Бабиченко, Анатолий Константинович; Тошинский, Владимир Ильич (НТУ "ХПИ", 2011)
As a result of researches by the mathematical design of ammonia synthesis sector the presence of the temperature optimum of the primary condensation was obtained. Apparatus and technological design of the additional refrigeration system was synthesized for providing of this temperature. Conducted researches were co nfirmed by partial introduction, that made it possible to decrease consumption expense norm of electric power on 19,4 kW per hour for a tone of ammonia.
Keywords: азотная промышленность; синтез аммиака; крупнотоннажные агрегаты; конденсация